1997
DOI: 10.1056/nejm199704243361704
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Selegiline, Alpha-Tocopherol, or Both as Treatment for Alzheimer's Disease

Abstract: In patients with moderately severe impairment from Alzheimer's disease, treatment with selegiline or alpha-tocopherol slows the progression of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,141
2
21

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,207 publications
(1,190 citation statements)
references
References 32 publications
26
1,141
2
21
Order By: Relevance
“…Protection against oxidative damage has already been demonstrated to slow the clinical progression of AD [28], and chelation therapy with the iron chelator desferrioxamine was able to reduce the disease progression in patients with sporadic AD [9]. The identification of this novel AD-related genetic determinant provides new insights into the pathogenesis of the disease, and may also contribute towards the diagnosis and treatment of individuals from families at risk of AD carrying HFE mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Protection against oxidative damage has already been demonstrated to slow the clinical progression of AD [28], and chelation therapy with the iron chelator desferrioxamine was able to reduce the disease progression in patients with sporadic AD [9]. The identification of this novel AD-related genetic determinant provides new insights into the pathogenesis of the disease, and may also contribute towards the diagnosis and treatment of individuals from families at risk of AD carrying HFE mutations.…”
Section: Discussionmentioning
confidence: 99%
“…But these drugs only offer a symptomatic approach and are of limited effect in long term administration. Other drugs have been reported to at least delay the progression of AD, like indomethacin (McGeer and McGeer, 1999;Rogers et al, 1993), selegilin and vitamin E (Sano et al, 1997), suggesting that anti-inflammatory and antioxidant agents can be beneficial in the treatment of AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple preclinical studies on vitamin C and vitamin E using transgenic AD mouse models indicated decreased lipid peroxidation, memory deficits, and Aβ plaque burden [114][115][116]. However, clinically, vitamins C and E showed limited benefits on cognitive function or delay of AD progression [117][118][119]141]. Some studies indicated negative effects of high-dose vitamin E on cognitive function and increased risk for mortality [142].…”
Section: Oxidative Damage As a Therapeutic Targetmentioning
confidence: 99%